Development of Nursing Management Learning Devices Based on A Scientific Approach to Maintain Science Process Skills During The Pandemic at Nursing Student of Stikes Hang Tuah Surabaya - Setiadi Setiadi; Imroatul Farida; Sri Anik Rustini; Dedi Irawandi (Asia Pacific Journal of Management and Education (APJME), 2021)
This research is development research that aims to develop learning tools for nursing management courses based on a scientific approach that is valid, practical, and effective for nursing students at Stikes Hang Tuah Surabaya to improve science process skills during a pandemic. The research parameters measured include device validity, practicality, and effectiveness. Data collection techniques comprise validation methods, observation and tests, and questionnaires. The results of the study indicate that the learning tools for nursing management courses based on a scientific approach are valid, practical, and effective.